ACCOUNTING IN A SINGLE INFORMATION SPACE OF THE ENTERPRISE (INNOVATIVE ECONOMY, 2021)
Skrypnyk S.V., Shepel I.V., Holovchak H.V. ACCOUNTING IN A SINGLE INFORMATION SPACE OF THE ENTERPRISEPurpose. The aim of the article is to study of accounting as an information system of enterprises for effective management decisions.Methodology of research. The study used general and special methods of cognition, in particular: methods of theoretical generalization and comparative analysis – for the analysis of relevant scientific literature; system approach, methods of analysis and synthesis – to substantiate the methodology of research of the accounting information system; generalization – in the study of current rules and regulations on the regulation of accounting, methods of reflecting its results and features of accounting processes in the enterprise; abstract and logical – in the generalization of theoretical positions and the formation of conclusions and proposals.Findings. The importance of disclosing the development and knowledge of accounting information and the impact it has on decision-making in small and medium-sized enterprises, as well as micro-enterprises, has been identified. It is established that the general economic development of the country requires adequate information, reliable and important for economic decisions from investors, managers, state administrators, etc. It is concluded that high-quality and reliable financial information is a key element in the decision-making process, in particular the availability of such information is of particular importance for business management and is generally in the public interest.Originality. The main factors of the influence of information support on the accounting of small enterprises are substantiated and revealed. The peculiarities of the practice of accounting systems that can be considered appropriate for small and medium enterprises in accordance with their specific circumstances and needs. It is suggested that an important factor influencing the construction of accounting in small business is the diversity of accounting systems.Practical value. The obtained results of the research allow to deepen the theoretical foundations and develop practical recommendations for improving the information support of accounting in small businesses, as well as to apply them for further research.Key words: small and medium enterprises, accounting, information, information system, financial reporting, decision making.
Keywords: Key words; small and medium enterprises; accounting; information; information system; financial reporting; decision making.